Influence of MHD Flow on Shrinking Sheet with Partial Slip and Heat Generation at Stagnation Point - Nurul Syuhada, Ismail; Norhunaini, Mohd Shaipullah; Siti Aishah, Azhar; Norihan, Md. Arifin; Norshafira, Ramli; Siti Suzilliana Putri, Mohamed Isa (Semarak Ilmu Publishing, 2025)
Fluid dynamics encompasses the fundamental principles of continuity, momentum, and energy conservation, which are applied through mathematical models like the Navier-Stokes equations. These equations are essential for describing how fluid properties like velocity, pressure, and density change in response to forces and environmental conditions. Thus, this study attempted to explore the characteristics of flow and heat transfer of a shrinking sheet in magnetohydrodynamics (MHD), along with the effect of partial slip and heat generation on the system. We employ a similarity transformation technique for turning the governing partial differential equations into ordinary differential equations. These equations are solved numerically through shooting method in Maple, and the results are compared to the previous research. The analysis shows that the suction parameter and velocity slip parameter have an increasing effect on both the skin friction rate and the heat transfer rate. In the meantime, the heat transfer rate decreases as the parameter increases for the heat generation, magnetic parameter, Eckert number and thermal slip parameter. The bvp4c solver in MATLAB is implemented to conduct a stability analysis and determine the physically feasible solution. According to our research, the stability of the solution occurs only in the first solution.